Dispersible cobalt chromite nanoparticles: facile synthesis and size driven collapse of magnetism. Issue 109 (11th November 2016) - Zakutna, D.; Matulkova, I.; Kentzinger, E.; Medlin, R.; Su, Y.; Nemkovski, K.; Disch, S.; Vejpravova, J.; Niznansky, D.
Abstract : Uniform nanoparticles of multiferoic CoCr2 O4 dispersible in non-polar solvents were prepared by hydrothermal route in water–alcohol–oleic acid system. Abstract : Multiferoic oxides have enormous application potential thanks to the mutually coupled magnetic and dielectric response embedded in a standalone material. Among them, the unique case is the cobalt chromite with spin-induced electric polarization locked to the magnetization direction and propagation vector of the spiral magnetic phase. The nature of the ground state magnetic structure gives rise to complex size dependent magnetic behaviour, which collapses when reaching a critical particle size. In our work, we focused on preparation of standalone cobalt chromite nanoparticles (NPs). We introduced hydrothermal decomposition of cobalt(ii )/chromium(iii ) oleates in a water/ethanol system without need of additional thermal treatment, which lead to stable cobalt chromite nanoparticles with diameter of 3.0(1)–4.2(1) nm and log normal size distribution of 12–16%. The size at the edge of the critical limit was tuned by the reaction temperature reaching typically 240 ± 10 °C. The as-prepared NPs are coated with covalently bonded oleic acid and can be easily dispersed in non-polar solvents, which makes them excellent candidates for custom surface modifications. The NPs were studied using a large number of characterization techniques: powder X-ray diffraction, transmission electron microscopy, small-angle X-ray scattering, and vibrational spectroscopies. The impact of the size effect on the magnetic properties was also investigated by temperature and magnetic field dependent magnetization, a.c. susceptibility and diffuse neutron scattering. The onset of the collective glassy state due to the collapse of long range conical magnetic order was observed. The uniform cobalt chromite NPs coated with oleic acid with size of 3–4 nm are excellent prototypes for studying the size effect on magnetic (and feroic) materials, and can be subjected to manifold surface functionalization required for their embedding in smart nanostructures and nanocomposites.